Intestinal Epithelial Barrier Dysfunction After Hemorrhagic Shock in a Rat Model - Ismeil, Abderrhman A.M.; A. Ishag, Abdulrahman; M. Warrag, Asma (Gezira Journal of Health Sciences, 2018)
Abstract:                                                                              Introduction: Hemorrhagic shock is a frequent complication in trauma patients, after gastrointestinal bleeding and major surgery. Hemorrhagic shock is associated with end organ damage, caused by hypoperfusion and local and systemic inflammation. The intestine is one of the first organs affected by hemorrhagic shock. An early event in intestinal damage is gut wall integrity loss, including the opening or breakdown of tight junctions. In this study,  the  sequence  of  events  in  the  gut  after hemorrhagic  shock  which  causing  tight  junction  loss  were  studied. Aim of the study: The aim of this study was to investigate the effect of the hemorrhagic shock on intestinal epithelial barrier function in a rat model. Material and Methods: This study was carried out on 40 male Wistar albino rats 4-6 months old with body weight (250-300g). Rats were divided randomly into four main groups: Group 1 (Control group): It consisted of 10 normal healthy rats served as control and sacrificed without intervention. Group 2 (30 minutes group): Consisted of 10 rats which were subjected to a non-lethal hemorrhagic shock. Rats were sacrificed (30 minutes) after the onset of hemorrhagic shock. Group 3 (60 minutes group): Consisted of 10 rats which were subjected to a non-lethal hemorrhagic shock. Rats were sacrificed (60 minutes) after the onset of hemorrhagic shock. Group 4 (90 minutes group): Consisted of 10 rats which were subjected to a non-lethal hemorrhagic shock and sacrificed (90 minutes) after the hemorrhagic shock. At the end of the study: Blood samples were collected for measurement of serum tumor necrosis factor alpha (TNF-a) and serum lipopolysaccharide (LPS). Distal segments of the ileum were excised immediately for histopathological study and measuring Zonula Occludens (ZO-1) gene expression. Results: TNF-α serum levels were significantly increased in all groups of hemorrhagic shock in comparison to their levels in the control group. Serum LPS levels measured in hemorrhagic groups showed significant increase in 60 and 90 min. groups when compared to the control group, while 30 min. group showed no significant change when compared to the control group. Histopathological study of the ileum segment revealed extension of the subepithelial space, focal mucosal infarction, a massive lifting down sides of the villi, some villus tips are denuded and epithelial cells are severely injured. PCR study of ZO-1 showed significant increase in ZO-1 gene expression in all groups of hemorrhagic shock as compared with the control group. Conclusion: This  study  gives  more  insight  into  the  sequence  of  events  in  the  gut  after  hemorrhagic shock. Hemorrhagic shock leads to intestinal tight junction integrity loss. This is followed by bacterial translocation and systemic inflammation.